Transforming collaborative narrative writing through storyboard that for ESL upper secondary school students - Subramaniam, Vanitha A/P; Ruhil Amal, Azmuddin (Penerbit UMPSA, 2024)
Writing, particularly narrative writing, is often challenging for upper secondary school students, especially when generating and organising ideas. The research addresses the challenge by integrating the ‘Storyboard That’, a web application that facilitates creative and collaborative writing through visual storytelling. It explores the role of technology in improving narrative writing skills among English as a Second Language (ESL) students. The research design involves an experimental design, with pre-and post-tests administered to control and experimental groups. Findings show that students in the experimental group who used the Storyboard That improved their narrative writing scores significantly compared to those in the control group. Also, students expressed positive feedback about the tool, noting its usefulness in brainstorming, organising plots, and enhancing creativity. This study highlights the importance of integrating technology in language education, mainly through collaborative and multimodal learning approaches. The Storyboard That application is a practical tool for improving ESL students’ writing skills by promoting active participation and creativity.